Estimation of health and economic benefits based on ozone exposure level with high spatial-temporal resolution by fusing satellite and station observations. (December 2019) - Liang, Shuang; Li, Xiaoli; Teng, Yu; Fu, Hongchen; Chen, Li; Mao, Jian; Zhang, Hui; Gao, Shuang; Sun, Yanling; Ma, Zhenxing; Azzi, Merched
Abstract: In recent years, ozone pollution has become more and more serious in China. Several epidemiological studies have demonstrated the correlation between short-term ozone exposure and several health risks including all-cause mortality, cardiovascular mortality, and respiratory mortality. In this study, the daily ozone exposure levels with 10 km × 10 km resolution were estimated based on satellite data derived from Ozone Monitoring Instrument (OMI) and the monitoring data. The health impacts for potential decrease in the daily ozone concentration and the corresponding economic benefits in 2016 were estimated by applying the environmental Benefits Mapping and Analysis Program-Community Edition (BenMAP-CE) model. By reducing the daily maximum 8-h average concentration of ozone to 100 μg/m 3, the estimated avoided all-cause mortalities were 120 × 10 3 (95% confidence interval (CI): 67 × 10 3, 160 × 10 3 ) cases and the correspondingly economic benefits ranged from 36 to 64 billion CNY using amended human capital (AHC) and willingness to pay (WTP) method in 2016. If the daily maximum 8-h average concentration of ozone were rolled back to 70 μg/m 3, the estimated avoided all-cause mortalities were 160 × 10 3 (95% CI: 98 × 10 3, 230 × 10 3 ) cases and economic benefits ranged from 54 to 95 billion CNY based on AHC and WTP methods. Graphical abstract: Image 1 Highlights: The ozone exposure level with high spatial-temporal resolution was simulated by fusing satellite and station observations. The avoided all-cause mortalities were 160 × 10 3 cases when the ozone daily exposure level reduced to the threshold value of 70 μg/m 3 in China, in 2016. The economic benefits related to avoided all-cause mortalities ranged from 36 to 95 billion CNY in China, in 2016.